Influence of Reaction Temperature on Optical Property of Mn-Doped ZnS Nanoparticles - Van, Bui Hong; Ben, Pham Van; Nhat, Hoang Nam (Communications in Physics, 2013)
The reaction temperature has essential effect on quality of the product synthesized by hydrothermal method. We report here the variation of the optical characteristics of Mn-doped ZnS nanocrystallites prepared by mean of the stated method from Zn(CH_3COO)_2.2H_2O, Mn(CH_3COO)_2.4H_2O and Na_2S_2O_3.5H_2O as the precursors. The reaction temperature was set to vary from 120C to 240C at a constant reaction time of 15 hours. The XRD patterns showed that, for the reaction temperature range from 120 to 160C, the obtained products possessed a cubic T_d^2 - F4 3m and a wurtzite C_6v^4 - P6_3 mcstructure, in which the cubic phase was dominant. At the temperature range from 180 to 240C, the structures exhibited a cubic phase with the lattice constant increased from 5.41 to 5.43 Å. The photoluminescence spectra showed that with the increase of reaction temperature from 120 to 240C the intensity of a blue band around 425 - 500 nm (attributed to both Zn, S vacancies) gradually decreased while the intensity of a yellow-orange band at 585 nm (attributed to the ^4T_1(^4G) - ^6A_1(^6S) transition of Mn^2 + ions) was enhanced and reached maximum at 220C. The excitation spectra of the 585 nm band recorded at 160C showed a band at 335 nm which should be assigned to the near band-edge absorption. With increasing temperature to 200-240C the new bands appeared at 390, 430, 467, 494 nm. The intensity of these bands increased with temperature and achieved the maxima at 220C. They should be attributed to the absorption transitions of electrons from ground state ^6A_1(^6S) to excited states^ 4E(^4D); ^4T_2(^4D); ^4A_1(^4G) - ^4E(^4G); ^4T_2(^4G) of Mn^2 + (3d^5) ions, respectively. The bands at 467, 494 nm only exposed clearly in the absorption spectra at 220C and 240C.